Description of the Risk of Heart Disease and Stroke in Residents of RW 03 Dampit, Malang, Based on Electrocardiogram and Fast Test Examination - Bambang Guruh Irianto; Dwi Herry Andayani; Sari Luthfiyah (Frontiers in Community Service and Empowerment, 2022)
The Malang regency district has the fourth-highest smoking prevalence rate among those over 10 years old, at 30%. 23.91% of the population aged 10 to 18 are active smokers who smoke daily. The number of passive smokers or people exposed to cigarette smoke is estimated to be higher than the number of smokers because when active smokers smoke, they also interact with non-smokers. Residents of Rukun Warga 03 Dampit village who suffer from hypertension and smoke are believed to have an impact on the incidence of heart disease and stroke, characterized by changes in the configuration of the ECG signal and signs of stroke. The purpose of this community service is to get an overview of the residents of RW.03 Dampit Village who have the potential to get heart diseases and strokes. The methodology used in conducting the community service under the community partnership program (PKM) is a pre-experimental single case study, i.e. the results of studying cardiac records of partners with a target of 50 residents in the RT environment. 007 RW. 03. The results of the community service activities showed that most (59%) reported ST elevation (ischemia) and 30% reported ST depression, the remaining 16% reported T elevation, and another 16% reported T depression. The results of his ECG recording showed evidence of M-shape, ST elevation, and ST depression (arrhythmia and ischemia). Meanwhile, all VES (ventricular extrasystoles) indicated are female. The conclusion from this community service is that there are more people who have the potential to get heart disease and stroke than active smokers. The benefits to the community are to know the condition of the residents of RW.03 Dampit Village who are potentially affected by heart disease and strokes and to improve residents' knowledge of the dangers of smoking for both active and passive smokers, the importance of eating healthy foods, and routine of exercise.